Exploring the Dimensions of Perfectionism in Adolescence: A Multi-Method Study on Mental Health and CBT-Based Psychoeducation - Magdalena Chęć; Krystian Konieczny; Sylwia Michałowska; Karolina Rachubińska (Brain Sciences)
Background: Perfectionism in adolescents can have both adaptive and maladaptive forms, with implications for mental health and school performance. This study aimed to investigate the relationships among perfectionism, mental health factors, and emotional regulation in adolescents and to evaluate the efficacy of psychoeducational interventions. Methods: Two studies were conducted: (1) A cross-sectional study (n = 261) examined the correlations among perfectionism, mental health factors, and emotional regulation. (2) An experimental study (n = 115) evaluated the effects of psychoeducation on perfectionism and healthy habits compared with a control group. The measures included questionnaires on perfectionism, depression, anxiety, stress, and emotional regulation. Results: Study 1 found that maladaptive perfectionism was positively correlated with depression (r = 0.52, p < 0.001), anxiety (r = 0.48, p < 0.001), stress (r = 0.45, p < 0.001), and difficulties in emotional regulation (r = 0.39, p < 0.001). Adaptive perfectionism was negatively correlated with deficits in emotional understanding (r = −0.31, p < 0.05). Study 2 showed that psychoeducational interventions reduced maladaptive perfectionism (mean difference = −5.7, p < 0.05, Cohen’s d = 0.62) and depression levels (mean difference = −3.2, p < 0.05, Cohen’s d = 0.38) but increased stress in the experimental groups. No significant changes were observed in adaptive perfectionism or the anxiety level. Conclusions: These findings highlight the complex relationships among perfectionism, mental health, and emotional regulation in adolescents. Targeted interventions can reduce maladaptive perfectionism and its associated negative effects. Further research is needed on the long-term outcomes and refinement of interventional strategies.